Development of a low-cost software for 2D deformation detection in geodetic network - Endot, Ernyza; Setan, Halim; Md. Som, Z. A. (2004)
Deformation monitoring in Malaysia has become more important nowadays due to the increasing risk of hazardous tragedies such as landslide, subsidence and structural movement in engineering structures. This paper focuses on the development of a low-cost software for deformation detection using Fredericton approach (2D applications). This in-house software (FREDY03) is developed under windows environment. Fredericton approach, which is based on the analysis of the invariant functions of displacements, concisely performs the analysis and least squares fitting of changes of distances and angles derived from the adjusted (minimum constraints) coordinates. This software consists of two modules: least square estimation (LSE) and deformation detection analysis. For verification, the results from FREDY03 are compared to our in-house software, DEFORM99 (via Congruency Testing). The results indicate that both approaches (Fredericton vs Congruency) give similar outcome on the stability status of the monitoring stations. Consequently, users can determine deformation detection between two epochs using the developed low-cost software.